Актуальные вопросы формирования билингвизма у детей в дошкольных учреждениях юго-восточного региона Украины - Лариса Ивановна Казанцева (International Dialogues on Education: Past and Present, 2016)
The article deals with the problem of Russian-Ukrainian bilingualism formation of preschool children under the conditions of the multicultural and multilingual environment of south-eastern Ukraine. It corresponds to the objective need to teach childrenthe Ukrainian language as a state language in preschool institutions with a predominantly Russian-speaking organization of the educational process. As it turned out, the process of bilingualism formation in children faces several contradictions arising between the sociolinguistic specifics of the South-Eastern region of the country and the linguistic situation in preschool institutions, between the actual level of preschool children’s knowledge of their native language and the Ukrainian language; between the level of language-consciousness development of children and the applied methodological tools of bilingualism formation. The most frequent errors in common practice in the formation of secondary phonetic, grammatical, dialogical, and communicative skills are singled out; the effective means of coping with cross-language interference, methodical ways of maximizing the positive impact of the transposition are named. Bilingualism formation in a multilingual environment can be successful if the training is based on the principles of reliance on pupils’ native language, on awareness and communication, taking into account the function of language units. The main conditions of bilingualism formation are the following: parity in the bilingual educational potential of preschool institutions’ speech environment; provision of conscious learning of a second language based on the native language; maximum immersion of children in the actual communicative speech and in language-play activities; the presence of positive emotional stimuli.